Cooling Effectiveness of Urban Green Infrastructure: A Review of Urban Heat Island Mitigation Strategy - Miftahul Huda; Respati Wikantiyoso; Aini, Nurul; Tutuko, Pindo (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The Urban Heat Island (UHI) phenomenon represents a significant environmental challenge in modern cities, intensifying air temperatures and degrading thermal comfort. Green Infrastructure (GI) has emerged as the primary intervention in mitigating this issue due to its capacity to provide shading, evapotranspiration cooling, and improved microclimatic balance. This study aims to synthesize existing research on GI-based UHI mitigation strategies by examining methodological approaches, cooling performance, influencing factors, and climatic context through a narrative review. A total of 31 peer-reviewed articles published between 2015 and 2025 were systematically identified using Publish or Perish. The results show that simulation-based approaches dominate the field, with ENVI-met forming the primary analytical tools, while empirical measurements remain crucial for calibration and validation. Across typologies, trees produce the strongest and most consistent cooling, followed by green walls and green roofs, whereas groundcovers provide the weakest cooling response for single interventions. However, it is important to note that multi-layered or combined GI configurations substantially outperform single-strategy approaches. Cooling outcomes are strongly shaped by vegetation characteristics, spatial configuration, hydrological and meteorological conditions, and the methodological frameworks used to measure cooling. Climatic context further mediates GI performance by influencing how strongly vegetation can express its shading and evapotranspirative functions across different environmental conditions. Overall, the review confirms that GI is an effective strategy for reducing urban heat and highlights the need for context-sensitive urban vegetation planning.